An elite family in early modern England : the Temples of Stowe and Burton Dassett, 1570-1656 - O'Day, Rosemary (Suffolk : Boydell & Brewer, 2018)
The Temples of Stowe were a leading Midland landed family, owning land in, and with strong connections to, Buckinghamshire, Leicestershire, Northamptonshire, Oxfordshire and Warwickshire. In the seventeenth century they were one of the wealthiest and most prominent local families, building in the eighteenth century a large and beautiful country house, now Stowe School. The family also left voluminous records, housed mainly in the Huntington and the Folger Shakespeare libraries. Based on very extensive research in these records, this book provides a detailed picture of the family life of the early Temples. It examines household, financial and estate management, discusses social networking and the promotion of family interests, and considers the legal disputes the family were engaged in. It focuses in particular on the happy and effective marriage of Sir Thomas and Lady Hester Temple, exploring their relationship with each other, with their children, and with their siblings. Lady Hester, who outlived her husband by twenty years, is a good example of a formidable matriarch, who took a strong lead in managing the family and its resources. Overall, the book provides a full and detailed picture of the family life of an aristocratic family in early modern England. ROSEMARY O'DAY is Professor of History at the Open University and author of, amongst numerous other works, Women's Agency in Early Modern Britain and the American Colonies: Patriarchy, Partnership and Patronage (Pearson. Longman 2007) and Cassandra Brydges (1670-1735) First Duchess of Chandos: Life and Letters (Boydell Press 2007).
Title from publisher's bibliographic system (viewed on 05 Jul 2018).
Keywords: Temple family; Elite (Social sciences) -- Great Britain -- History; Great Britain -- History -- Elizabeth, 1558-1603.; Great Britain -- History -- Stuarts, 1603-1714.